Adjunctive thyroid hormone treatment in rapid cycling bipolar disorder: A double‐blind placebo‐controlled trial of levothyroxine (L‐T4) and triiodothyronine (T3). (4th June 2018) - Walshaw, Patricia D; Gyulai, Laszlo; Bauer, Michael; Bauer, Mark S; Calimlim, Brian; Sugar, Catherine A; Whybrow, Peter C
Abstract : Objectives: This report describes the first comparative double‐blind, placebo‐controlled trial of levothyroxine (L‐T4 ) and triiodothyronine (T3 ) as adjunctive treatments in rapid cycling bipolar disorder. Methods: Thirty‐two treatment‐resistant, rapid cycling patients who had failed a trial of lithium were randomized into three treatment arms: L‐T4, T3, or placebo. They were followed for ≥4 months with weekly clinical and endocrine assessments. Results: There were no statistically significant differences between the groups in age, gender, duration of illness, or thyroid status. Markov chain analyses were employed to assess treatment effects on cycling patterns among mood states (euthymia, depression, mania, and mixed). Within groups, post‐treatment the L‐T4 group spent significantly less time depressed or in a mixed state and greater time euthymic. The T3 and placebo groups did not differ significantly pre‐ and post‐treatment in any mood state, although the pattern of effects was the same for the T3 group as for the L‐T4 group. Between groups, the L‐T4 group had a significantly greater increase in time euthymic and decrease in time in the mixed state than the placebo group. Other group differences were not significant, although they were in the expected direction. Conclusions: The findings in this first double‐blind study directly comparing the effects of L‐T4 and T3 therapy against placebo provide evidence for the benefit of adjunctive L‐T4 in alleviating resistant depression, reducing time in mixed states and increasing time euthymic. Adjunctive T3 did not show statistically significant evidence of benefit over placebo in reducing the time spent in disturbed mood states.